STUDY THE GENETIC BEHAVIOR FOR SOME GENOTYPES OF MUSKMELON - Kamal B. Esho (European Journal of Agricultural and Rural Education, 2023)
The genetic parameters regarding seven muskmelons (melon) genotypes—Meloky, Alqoshy, Walaty, Se-jeqal, Mostaqbal, Pineapple, and Hales best Jumbo—were studied in vegetable field of the Dept. of Horticulture and Landscape Engineering, College of Agriculture and Forestry, Univ. of Mosul throughout the spring of 2021 agricultural season. The study’s most significant findings were summed up, and in the case when examining the sources of variation that genotypes differed, these results were analyzed. Significant differences were observed between them in the majority of traits examined at the probability 5% level for Duncan’s polynomial test. Cultivar 7 outperformed the other genotypes in the trait of having more fruits in the plant, while genotype 2 outperformed the other genotypes in the traits of having the largest total yield per unit area (Dunum) and a weight of 100 seeds. Additionally, the proportion of heritability in the broadest sense has been high for all examined traits, exceeding 50%, and the phenotypic and genetic variation has been high for the traits of the weight of the fruit and seeds for each fruit, herb length, and the total seed output per unit area. The majority of variables under study showed favorable phenotypic and genetic correlations with the overall fruit yield per unit area